Highly ordered ultralong magnetic nanowires wrapped in stacked graphene layers - El Mel, Abdel-Aziz; Duvail, Jean-Luc; Gautron, Eric; Xu, Wei; Choi, Chang-Hwan; Angleraud, Benoit; Granier, Agnès; Tessier, Pierre-Yves (Beilstein Journal of Nanotechnology, 2012)
We report on the synthesis and magnetic characterization of ultralong (1 cm) arrays of highly ordered coaxial nanowires with nickel cores and graphene stacking shells (also known as metal-filled carbon nanotubes). Carbon-containing nickel nanowires are first grown on a nanograted surface by magnetron sputtering. Then, a post-annealing treatment favors the metal-catalyzed crystallization of carbon into stacked graphene layers rolled around the nickel cores. The observed uniaxial magnetic anisotropy field oriented along the nanowire axis is an indication that the shape anisotropy dominates the dipolar coupling between the wires. We further show that the thermal treatment induces a decrease in the coercivity of the nanowire arrays. This reflects an enhancement of the quality of the nickel nanowires after annealing attributed to a decrease of the roughness of the nickel surface and to a reduction of the defect density. This new type of graphene–ferromagnetic-metal nanowire appears to be an interesting building block for spintronic applications.
Keywords: carbon; ferromagnetic; graphene; nanofabrication; nanowires; nickel; phase separation

(untitled) - Piraux, L.; George, J. M.; Despres, J. F.; Leroy, C.; Ferain, E.; Legras, R.; Ounadjela, K.; Fert, A. (Appl. Phys. Lett., 1994)

(untitled) - Dubois, S.; Marchal, C.; Beuken, J. M.; Piraux, L.; Duvail, J. L.; Fert, A.; George, J. M.; Maurice, J. L. (Appl. Phys. Lett., 1997)

(untitled) - Piraux, L.; Dubois, S.; Duvail, J. L.; Ounadjela, K.; Fert, A. (J. Magn. Magn. Mater., 1997)

(untitled) - Ferré, R.; Ounadjela, K.; George, J. M.; Piraux, L.; Dubois, S. (Phys. Rev. B, 1997)

(untitled) - Zheng, M.; Menon, L.; Zeng, H.; Liu, Y.; Bandyopadhyay, S.; Kirby, R. D.; Sellmyer, D. J. (Phys. Rev. B, 2000)

(untitled) - Whitney, T. M.; Searson, P. C.; Jiang, J. S.; Chien, C. L. (Science, 1993)

(untitled) - Lorcy, J. M.; Massuyeau, F.; Moreau, P.; Chauvet, O.; Faulques, E.; Wéry, J.; Duvail, J. L. (Nanotechnology, 2009)

(untitled) - Darques, M.; De la Torre Medina, J.; Piraux, L.; Cagnon, L.; Huynen, I. (Nanotechnology, 2010)

(untitled) - Fung, A. O.; Kapadia, V.; Pierstorff, E.; Ho, D.; Chen, Y. (J. Phys. Chem. C, 2008)

(untitled) - Gao, N.; Wang, H.; Yang, E.-H. (Nanotechnology, 2010)

(untitled) - Nautiyal, T.; Rho, T. H.; Kim, K. S. (Phys. Rev. B, 2004)

(untitled) - Thurn-Albrecht, T.; Schotter, J.; Kästle, G. A.; Emley, N.; Shibauchi, T.; Krusin-Elbaum, L.; Guarini, K.; Black, C. T.; Tuominen, M. T.; Russell, T. P. (Science, 2000)

(untitled) - Geim, A. K.; Novoselov, K. S. (Nat. Mater., 2007)

(untitled) - Geim, A. K. (Science, 2009)

(untitled) - Guttmann, P.; Bittencourt, C.; Rehbein, S.; Umek, P.; Ke, X.; Van Tandeloo, G.; Ewels, C. P.; Schneider, G. (Nat. Photonics, 2012)

(untitled) - Wagner, P.; Ewels, C. P.; Ivanovskaya, V. V.; Briddon, P. R.; Pateau, A.; Humbert, B. (Phys. Rev. B, 2011)

(untitled) - Wang, X.; Zhi, L.; Mullen, K. (Nano Lett., 2008)

(untitled) - Stoller, M. D.; Park, S.; Zhu, Y.; An, J.; Ruoff, R. S. (Nano Lett., 2008)

(untitled) - Lin, Y.-M.; Jenkins, K. A.; Valdes-Garcia, A.; Small, J. P.; Farmer, D. B.; Avouris, P. (Nano Lett., 2009)

(untitled) - Camilli, L.; Scarselli, M.; Del Gobbo, S.; Castrucci, P.; Lamastra, F. R.; Nanni, F.; Gautron, E.; Lefrant, S.; D’Orazio, F.; Lucari, F.; De Crescenzi, M. (Carbon, 2012)

(untitled) - Zeeshan, M. A.; Shou, K.; Pané, S.; Pellicer, E.; Sort, J.; Sivaraman, K. M.; Baró, M. D.; Nelson, B. J. (Nanotechnology, 2011)

(untitled) - Wang, R.; Hao, Y.; Wang, Z.; Gong, H.; Thong, J. T. L. (Nano Lett., 2010)

(untitled) - Gao, X. P.; Zhang, Y.; Chen, X.; Pan, G. L.; Yan, J.; Wu, F.; Yuan, H. T.; Song, D. Y. (Carbon, 2004)

(untitled) - Topsakal, M.; Şahin, H.; Ciraci, S. (Phys. Rev. B, 2012)

(untitled) - El Mel, A. A.; Gautron, E.; Angleraud, B.; Granier, A.; Xu, W.; Choi, C. H.; Briston, B. J.; Inkson, B. J.; Tessier, P. Y. (Nanotechnology, 2012)

(untitled) - El Mel, A. A.; Bouts, N.; Grigore, E.; Gautron, E.; Granier, A.; Angleraud, B.; Tessier, P. Y. (J. Appl. Phys., 2012)

(untitled) - Choi, C.-H.; Kim, C.-J. (Nanotechnology, 2006)

(untitled) - Hamaguchi, S.; Rossnagel, S. M. (J. Vac. Sci. Technol., B, 1995)

(untitled) - El Mel, A. A.; Gautron, E.; Angleraud, B.; Granier, A.; Tessier, P. Y. (Carbon, 2011)

(untitled) - Allouche, H.; Monthioux, M. (Carbon, 2005)

(untitled) - Baraton, L.; He, Z.; Lee, C. S.; Maurice, J.-L.; Cojocaru, C. S.; Gourgues-Lorenzon, A.-F.; Lee, Y. H.; Pribat, D. (Nanotechnology, 2011)

(untitled) - Lander, J. J.; Kern, H. E.; Beach, A. L. (J. Appl. Phys., 1952)

(untitled) - Zheng, M.; Takei, K.; Hsia, B.; Fang, H.; Zhang, X.; Ferralis, N.; Ko, H.; Chueh, Y.-L.; Zhang, Y.; Maboudian, R.; Javey, A. (Appl. Phys. Lett., 2010)

(untitled) - Garaj, S.; Hubbard, W.; Golovchenko, J. A. (Appl. Phys. Lett., 2010)

(untitled) - Encinas-Oropesa, A.; Demand, M.; Piraux, L.; Huynen, I.; Ebels, U. (Phys. Rev. B, 2001)

(untitled) - Encinas-Oropesa, A.; Demand, M.; Piraux, L.; Ebels, U.; Huynen, I. (J. Appl. Phys., 2001)

(untitled) - Demand, M.; Encinas-Oropesa, A.; Kenane, S.; Ebels, U.; Huynen, I.; Piraux, L. (J. Magn. Magn. Mater., 2002)

(untitled) - Martín, J. I.; Nogués, J.; Liu, K.; Vincent, J. L.; Schuller, I. K. (J. Magn. Magn. Mater., 2003)

(untitled) - Adeyeye, A. O.; Bland, J. A. C.; Daboo, C.; Lee, J.; Ebels, U.; Ahmed, H. (J. Appl. Phys., 1996)

(untitled) - Blundell, S. J.; Shearwood, C.; Gester, M.; Baird, M. J.; Bland, J. A. C.; Ahmed, H. (J. Magn. Magn. Mater., 1994)

(untitled) - Adeyeye, A. O.; Bland, J. A. C.; Daboo, C.; Hasko, D. G.; Ahmed, H. (J. Appl. Phys., 1997)

(untitled) - Adeyeye, A. O.; Bland, J. A. C.; Daboo, C.; Hasko, D. G. (Phys. Rev. B, 1997)

(untitled) - Adeyeye, A. O.; Bland, J. A. C.; Daboo, C. (J. Magn. Magn. Mater., 1998)

(untitled) - Schabes, M. E. (J. Magn. Magn. Mater., 1991)